Biomechanical comparison of three different compression screws for treatment of odontoid fractures evaluation of a new screw design. (July 2020) - Müller, Jan-Uwe; Müller, Jonas; Marx, Sascha; Matthes, Marc; Nowak, Stephan; Schroeder, Henry Werner Siegfried; Pillich, Dirk Thomas
Abstract: Background: Lag screw osteosynthesis in odontoid fractures shows a high rate of pseudarthrosis. Biomechanical properties may play a role with insufficient fragment compression or unnoticed screw stripping. A biomechanical comparison of different constructed lag-screws was carried out and the biomechanical properties determined. Methods: Two identical compression screws with different pilot holes (1.25 and 2.5 mm), a double-threaded screw and one sleeve-nut-screw were tested on artificial bone (Sawbone, densities 10-30pcf). Fragment compression and torque were continuously measured using thin-film force sensors (Flexiforce A201, Tekscan) and torque sensors (PCE-TM 80, PCE GmbH). Findings: The lowest compression reached the double-threaded screw. Compression and sleeve-nut-screw achieved 214–298% and 325–546%, respectively, of the compression force of double-threaded-screw, depending on the test material. The pilot hole optimization led to a significant improvement in compression only in the densest test material. Screw stripping took place significantly later with increasing density of the test material on all screws. In compression screws this was done at a screw rotation of 180–270°, in sleeve nut screw at 270–720° and in double-threaded screws at 300–600° after reaching the maximum compression. Interpretation: Double-threaded screw is robust against screw stripping, but achieves only low fragment compression. The classic compression screws achieve better compression, but are sensitive to screw stripping. Sleeve-nut screw is superior in compression and as robust as double-threaded screw against screw stripping. Whether the better biomechanical properties lead to a reduction in pseudarthrosis must be proven in clinical trials. Highlights: The quotient of maximum and plateau torque can be improved by optimal predrilling. The application torque can be indicative of the stripping torque. Compression force and torque are correlated for compression and sleeve-nut screws. Double-threaded and sleeve-nut screws show a higher tolerance to screw tearing. Sleeve-nut screw is superior in compression.